Problems of Qibla Direction Shift Due to Earth Plate Shift in Indonesia - Mutrofin, Akmam; Syarifah, Faradhina Millatul Maula; Sundari, Titin; Dimyati, Yayat; Hidayat, Rohmat (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. Facing the Qibla is a requirement for valid prayer. There is an issue of shifting the direction of the Qibla in Indonesian mosques due to an earthquake. The Indonesian Ulema Council (MUI) held a hearing and issued a fatwa. The fatwa caused public unrest because it did not comply with the agreement of experts in the science of Falak and Astronomy. Aim. This article aims to straighten out the controversy over the direction of the Qibla which appears to have shifted due to an earthquake and provide solutions to resolve problems related to changes in the direction of the qibla in mosques in Indonesia. Methods. Literature study takes data from primary data sources (Lajnah Falakiyah, Falak experts, books by classical and contemporary ‘ulemas that specifically discuss the Qibla), and; secondary data sources (books, journals, and notes that are relevant to the study of the Qibla). The data are analyzed using content analysis to make inferences objectively and systematically. Results. The shifting of the earth’s plates only affects changes in the earth’s map in a time span of tens or hundreds of millions of years, and will not have a significant impact on changes in the direction of the Qibla outside Makkah in the span of current human civilization.